1997
DOI: 10.3109/00365599709070348
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Concentration and PTH Levels. Is Long-Term Chronic Hypermagnesemia a Risk Factor for Adynamic Bone Disease?

Abstract: The observation that some subjects with low PTH had elevated plasma magnesium (Mg) levels prompted us to analyze in 41 patients on maintenance hemodialysis for 44 +/- 36 months, their serum Mg concentrations, and the relationship between plasma Mg and PTH levels. The mean serum Mg concentration was 2.4 +/- 0.2 mg/dl. Twenty-four out of the 41 subjects (58.5%) had hypermagnesemia (serum Mg above 2.5 mg/dl). Patients were classified into 3 groups according to their PTH level: Group A, low PTH (below 120 pg/ml); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…It has been recently noted that in end-stage kidney disease chronically increased levels of total magnesium decrease parathyroid hormone levels and predispose to a dynamic bone disease [15, 16]. It has therefore been suggested to reduce the magnesium dialysate concentration at least in this peculiar situation [15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recently noted that in end-stage kidney disease chronically increased levels of total magnesium decrease parathyroid hormone levels and predispose to a dynamic bone disease [15, 16]. It has therefore been suggested to reduce the magnesium dialysate concentration at least in this peculiar situation [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently noted that in end-stage kidney disease chronically increased levels of total magnesium decrease parathyroid hormone levels and predispose to a dynamic bone disease [15, 16]. It has therefore been suggested to reduce the magnesium dialysate concentration at least in this peculiar situation [15, 16]. The results of the present study confirm that the total and the free levels of magnesium often do not go hand in hand and demonstrate that in this condition the total concentration of magnesium mostly overestimates that of ionized magnesium, the most attractive form with respect to biological properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)  Magnesium: Navarro et al noted a significant negative correlation between serum magnesium and PTH, both in hemodialysis [54, 55]and CAPD patients [56, 57]. Magnesium affects PTH in a similar way to calcium [58, 59].…”
Section: An Iatrogenic Disease?mentioning
confidence: 99%
“…Several past studies have suggested that hypermagnesemia, by increasing total body and bone magnesium, may lead to worsening of renal osteodystrophy [4], delayed nerve conduction [5], and pruritus [6], and that lowering plasma [Mg] can improve these abnormalities [4,5,6]. More recently, use of magnesium as an inexpensive phosphate binder [7,8,9,10,11] and the possible role of high magnesium in adynamic bone disease [12] have led to use of a lower dialysate [Mg]. Whereas mild hypermagnesemia is expected with use of a dialysate [Mg] of 1.5 mEq/l [13,14,15,16], a dialysate [Mg] of 1.0 mEq/l has generally been associated with either normal plasma [Mg] or mild hypermagnesemia [17,18].…”
Section: Introductionmentioning
confidence: 99%